Efficacy of statin on vascular access patency in diabetic hemodialysis patients. Issue 4 (July 2017) - Sanada, Satoru; Miyasaka, Yasunori; Kanno, Atsuhiro; Sato, Kozo; Sato, Mitsuhiro; Sugai, Hisako; Kitamura, Hiroshi; Sato, Toshinobu; Taguma, Yoshio
Introduction: An effective approach to prevent hemodialysis vascular access dysfunction is still unclear despite previous studies, which have shown conflicting results of several drugs on vascular access outcomes. In this study, we focused on diabetic hemodialysis patients with native arteriovenous fistula and evaluated the impact of statin treatment on vascular access patency. Methods: A retrospective cohort study of 268 consecutive patients who newly started hemodialysis due to diabetic nephropathy between January 2011 and December 2013 at Japan Community Health Care Organization Sendai Hospital was performed and the patients were followed for two years. The primary outcome was vascular access dysfunction. Effect of statin treatment was examined using Kaplan Meier analysis and Cox proportional hazard, after adjusting for covariates. Results: The mean follow-up period was 426.7 days, and 117 (52.2%) patients developed vascular access dysfunction. The two-year patency rate was 55.0% among statin users and 36.1% in non-users. Vascular access survival period was significantly longer among statin users (log-rank test, p = 0.004). In multivariable analysis, statin treatment is significantly associated with better vascular access outcomes, in which the hazard ratio was 0.71 (95% CI, 0.52 to 0.97; p = 0.028) in the unadjusted model and 0.63 (95% CI, 0.45 to 0.88; p = 0.007) after adjustment for covariates. Conclusions: Statin treatment could be associated with improved vascular access dysfunction among diabetic hemodialysis patients.